The Relationship Between Mental Workload, Noise, Individual Characteristics and Work Stress among Workers at PT. PLN Nusantara Power UP Muara Tawar - Kania Fitrianti Zahrah; Ida Wahyuni; Ekawati Ekawati (Journal Occupational Health Hygiene and Safety, 2025)
Work environments demanding high productivity often ignore workers' psychological aspects, triggering work stress. Job stress is an individual's response to work pressure exceeding their coping ability. A main cause is mental workload—an individual's perception of task weight to be completed within certain time and conditions. Additionally, workplace noise can worsen psychological conditions, especially if continuous. Individual characteristics such as age, length of service, and education level also determine a person's vulnerability to stress. These factors, if not properly managed, can negatively impact worker health, safety, and productivity. This study analyzed the relationship between mental workload, noise, individual characteristics, and work stress using quantitative methods with cross-sectional design. The population comprised 134 workers in noise areas divided into 4 fields: operators, machine maintenance, electrical maintenance, and control & instrument maintenance. Using proportionate stratified sampling and accidental sampling techniques, 60 samples were obtained. Results showed 76.7% of respondents experienced moderate work stress, with the most dominant cause being qualitative overload (33.3%). Chi-square test analysis revealed a relationship between mental workload and work stress (p-value = 0.003). However, noise (p-value = 0.422), age (p-value = 0.512), length of service (p-value = 0.259), and education level (p-value = 0.201) were not related to work stress. In conclusion, there is a significant relationship between mental workload and work stress among workers at PT. PLN Nusantara Power UP Muara Tawar. Therefore, it is important for companies to identify and manage stress-inducing factors to create a healthy and sustainable work environment.